Acute disseminated encephalomyelitis after mumps infection in a vaccinated patient. (2021) - Gonçalves, Raquel; Gomes, João; Martins, André; Duque, Vitor; Lemos, João Manuel; Trindade, Luís
Abstract: Mumps is an infectious disease caused by a paramyxovirus. It can involve several organs in the acute stage of the infection, including central nervous system. (Rubin et al., 2015) [1 ] Neurological complications in the post-infectious period are also described, one of which is acute disseminated encephalomyelitis (ADEM). (Jonhson et al., 2004) [2 ] We present the case of an healthy young man previously vaccinated, who contracted ADEM after mumps.